Staging Brazil : Choreographies of Capoeira - Höfling, Ana Paula (Book collections on Project MUSE., 2019)
Staging Brazil: Choreographies of Capoeira is the first in-depth study of the processes of legitimization and globalization of capoeira, the Afro-Brazilian combat game practiced today throughout the world. Ana Paula Höfling contextualizes the emergence of the two main styles of capoeira, angola and regional, within discourses of race and nation in mid-twentieth century Brazil. This history of capoeira's corporeality, on the page and on the stage, includes analysis of illustrated capoeira manuals and reveals the mutual influences between capoeira practitioners, tourism bureaucrats, intellectuals, artists, and directors of folkloric ensembles. Staging Brazil sheds light on the importance of capoeira in folkloric shows in the 1960s and 70s--both those that catered to tourists visiting Brazil and those that toured abroad and introduced capoeira to the world.